The Quandary of Identity in Lisa KO's The Leavers (2017) - Bryan Tirannov; Desvalini Anwar (English Language and Literature, 2023)
"The Leavers" is a novel written by Lisa Ko, published in 2017, which tells the story of Deming Guo, an eleven-year-old boy who is adopted by a couple in New York after his mother, an undocumented Chinese immigrant, disappears. The novel explores themes of identity, family, and belonging, as Deming struggles to come to terms with his mother's disappearance and his new identity as Daniel Wilkinson. The novel has been widely praised for its portrayal of the experiences of immigrants and the children of immigrants in the United States. It deals with themes of identity, discrimination, fear of deportation, and the pursuit of the American Dream. The novel provides a nuanced look at the realities of immigration and the struggles that immigrants face in pursuit of the American Dream. It's a powerful and thought-provoking novel that deals with important and timely issues.